Mengukir Kebahagiaan dalam Pola Hidup Sederhana, Mungkinkah? - Jodi Wahyudi; Desiyana (Yayasan Aya Sophia Indonesia, 2023)
The purpose of this research is to review books to explore and understand the scientific narrative of the book